2006
DOI: 10.1128/iai.00815-06
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinations with Recombinant Variants of Aspergillus fumigatus Allergen Asp f 3 Protect Mice against Invasive Aspergillosis

Abstract: A vaccine that effectively protects immunocompromised patients against invasive aspergillosis is a novel approach to a universally fatal disease. Here we present a rationale for selection and in vivo testing of potential protein vaccine candidates, based on the modification of an immunodominant fungal allergen for which we demonstrate immunoprotective properties. Pulmonary exposure to viable Aspergillus fumigatus conidia as well as vaccination with crude hyphal extracts protects corticosteroid-immunosuppressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
86
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 44 publications
6
86
0
10
Order By: Relevance
“…By showing their Th2 promoting activity, the present study confirms the allergenic potential of the secreted proteins (12,14). However, the vaccinating potential of some allergens, including secreted proteases (37), have also been described (8,11). Although the secretion of aspartic proteases has long been recognized as a virulence-associated trait of Candida spp.…”
Section: Discussionsupporting
confidence: 55%
“…By showing their Th2 promoting activity, the present study confirms the allergenic potential of the secreted proteins (12,14). However, the vaccinating potential of some allergens, including secreted proteases (37), have also been described (8,11). Although the secretion of aspartic proteases has long been recognized as a virulence-associated trait of Candida spp.…”
Section: Discussionsupporting
confidence: 55%
“…Therefore, previously, we engineered truncated nonallergen versions of rAsp f3 that lacked the IgEbinding epitope and protected immunosuppressed mice against aspergillosis. The rAsp f3 variant that spans residues 15 to 168, Asp f3(15-168), elicited better protection (83%) than full-length rAsp f3(1-168) (25).…”
mentioning
confidence: 99%
“…Asp f3 is a putative peroxisomal protein and was identified as a potential vaccine candidate by mass spectrometric analysis of antigens that bound to antibodies from immunocompetent mice after pulmonary exposure to nonlethal doses of A. fumigatus conidia (25). The Asp f3 protein has also been described as a major allergen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…68 The group subsequently reported that sera from the vaccinated animals contained antibodies against Asp f3. 69 The vaccination of Asp f3 was effective to prevent the subsequent Aspergillus infection in corticosteroid-treated mice. CD4…”
Section: Importance Of Immunity Against Aspergillus Infectionsmentioning
confidence: 99%